Organizational strategies Induced by the fourth industrial revolution: workforce awareness and realignment - Gaspar, Marcelo (2018)
“This is a post-peer-review, pre-copyedit version of an article published in Lecture Notes in Electrical Engineering. The final authenticated version is available online at: https://doi.org/10.1007/978-3-319-91334-6_45"